2005
DOI: 10.1111/j.1540-8159.2005.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of the Fall of Impedance as the Result of Heating During Ostial Pulmonary Vein Ablation: Implications for Power Titration

Abstract: An increased impedance fall as the result of heating during ostial ablation was found inside the proximal pulmonary veins as compared to atrial sites. Adjusting power to the fall of impedance during segmental ostial pulmonary vein ablation contributes to the prevention of overheating inside the pulmonary veins and may lower the risk of coagulum formation and pulmonary vein stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 48 publications
(50 reference statements)
1
33
0
Order By: Relevance
“…Strickberger and colleagues 10 correlated impedance drop with catheter electrode temperature and the presence of thrombus on the catheter in 33 patients undergoing RF ablation of accessory pathways with a 4‐mm tip thermistor tipped catheter. They found that an impedance drop of 5–10 Ω appeared optimal (effective tissue heating and low rate of thrombus), whereas RF applications that were associated with thrombus formation had a mean impedance drop of 19 Ω. Reithmann and colleagues 7 investigated the use of impedance‐controlled ablation using a 4‐mm tip ablation catheter in 70 patients undergoing pulmonary vein isolation procedures. Power was titrated to achieve an impedance drop of 20 Ω with a low rate of impedance rises (0.3%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strickberger and colleagues 10 correlated impedance drop with catheter electrode temperature and the presence of thrombus on the catheter in 33 patients undergoing RF ablation of accessory pathways with a 4‐mm tip thermistor tipped catheter. They found that an impedance drop of 5–10 Ω appeared optimal (effective tissue heating and low rate of thrombus), whereas RF applications that were associated with thrombus formation had a mean impedance drop of 19 Ω. Reithmann and colleagues 7 investigated the use of impedance‐controlled ablation using a 4‐mm tip ablation catheter in 70 patients undergoing pulmonary vein isolation procedures. Power was titrated to achieve an impedance drop of 20 Ω with a low rate of impedance rises (0.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The impedance fall that occurs during RF ablation has been postulated to be caused by an increase in tissue temperature, 7,8,10,12 but some authors have detected irreversible changes in components of the impedance 11 . Data recorded during repeated ablations at the same site suggested that the impedance drop occurring during radiofrequency ablation in cardiac tissue appeared to be due to reversible factors (e.g., temperature) rather than irreversible changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Prior clinical and experimental studies have found an impedance decrease from baselines of at least 5 O to 10 O to be best associated with effective tissue destruction, regardless of the baseline tissue characteristics. 12,14,15 Impedance monitoring can also guide the duration of lesion application, as lesion expansion may continue for 10 s following reaching the plateau of the impedance curve. 16 Additionally, impedance monitoring has an additional important role for monitoring safety of RF energy application, as steam pops are rarely seen when the impedance decrease is less than 15 ohms (O).…”
Section: Rf Lesion Assessmentmentioning
confidence: 99%
“…8 A linearly increasing fall in impedance with an increasing catheter tip temperature has been described for nonirrigated ablation. 4,9,10 This has been suggested to be because of increased conductivity of cardiac tissue with heating.…”
Section: Discussionmentioning
confidence: 99%